Effect of COVID-19 pandemic on serious mental illness-related outpatient department utilization in Ningbo, China: an interrupted time series analysis - Lian Li; Hongying Yang; Rongxiang Zhang; Yucheng Wang; Guolin Bian (Frontiers in Psychiatry, 2023)
BackgroundGlobally, the coronavirus disease 2019 (COVID-19) pandemic has negatively affected mental health services, but there is no clear evidence of this in China. Therefore, we examined the effect of the COVID-19 pandemic on the use of serious mental illness (SMI)-related outpatient services in Ningbo, China.MethodsWe analyzed the trends in monthly SMI-related outpatient department utilization from January 2018 to June 2022 using interrupted time series (ITS) regression analysis, and we defined the onset of the COVID-19 pandemic as January 2020. We also performed ITS regression analyses for sex and age subgroups.ResultsA significant difference in the monthly number of outpatient visit slopes before and after the onset of the pandemic was shown in the SMI analysis [−175.6, 95% confidence interval (CI) (−338.3 to −12.9), p < 0.05]. All sex and age categories, except the 20–30 years age category, showed statistically significant changes in their slopes after the onset of the pandemic. Significant differences in the number of outpatient visit slopes before and after the onset of the pandemic were seen for schizophrenia and bipolar disorders [−153.3, 95% CI (−294.1 to −12.5) and −16.8 (−31.0 to −2.6), respectively]. Moreover, a negative relationship was observed between the monthly number of outpatient visits and the number of incidents and accidents due to SMI (r = −0.38, p < 0.05).ConclusionThe COVID-19 pandemic has had a negative effect on SMI-related outpatient visits in Ningbo, especially by patients with schizophrenia. A strategy should be developed and implemented to maintain access to SMI services during the COVID-19 pandemic.